Consideration of Cosmetic Surgery As Part of Women’s Benefit-Provisioning Mate Retention Strategy - Atari, Mohammad; Barbaro, Nicole; Sela, Yael; Shackelford, Todd K.; Chegeni, Razieh (Frontiers in Psychology, 2017)
Individuals perform mate retention behaviors to minimize the risk of partner infidelity and relationship dissolution. The current study investigates whether consideration of cosmetic surgery can be conceptualized as part of a broader strategy of mate retention for women, but not men. We hypothesized that women’s consideration of cosmetic surgery would be positively associated with performance frequencies of Benefit-Provisioning and Cost-Inflicting mate retention behaviors. We recruited 203 individuals (54% women) in committed heterosexual relationships from Tehran, Iran. Results indicate a positive association between consideration of cosmetic surgery and Benefit-Provisioning mate retention behaviors for women, but not men. There was no association between consideration of cosmetic surgery and Cost-Inflicting mate retention behaviors. Women therefore may consider cosmetic surgery to improve their physical attractiveness as part of a Benefit-Provisioning strategy to retain a long-term mate. We discuss limitations of the study and highlight future directions for research from an evolutionary perspective.